2020
DOI: 10.1111/ics.12605
|View full text |Cite
|
Sign up to set email alerts
|

A novel water‐in‐oil emulsion with a lecithin‐modified bentonite prevents skin damage from urban dust and cedar pollen

Abstract: OBJECTIVE: Particulate matter (PM), such as air pollutants and pollens, are known to cause skin ageing through skin inflammation. It is important to develop formulations which protect the skin from PM. We previously developed a conventional water-in-oil emulsion with a synthetic surfactant, distearyldimonium chloride, modified bentonite (C-W/O), which protects skin from allergens. In the present study, we developed a novel water-in-oil emulsion with a natural surfactant, lecithin, modified bentonite (N-W/O). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In 3D HEE models, PM usually in concentrations of up to 50 μg/mL was mainly applied topically and short-term exposures (i.e., 24 to 48 h) were performed [128,130,132,133]. PM was shown to affect the physical epidermal barrier in 3D models, as indicated by altered expression of proteins important for epidermal differentiation, such as filaggrin, involucrin, loricrin, and keratins [125,127,129,130,132,133]. Additionally, markers for proliferation, such as Ki67, 5-bromo-2′-deoxyuridine (BrdU) incorporation, and proliferating cell nuclear antigen (PCNA), were shown to be decreased upon PM exposure [125,130].…”
Section: Physical Barriermentioning
confidence: 99%
See 2 more Smart Citations
“…In 3D HEE models, PM usually in concentrations of up to 50 μg/mL was mainly applied topically and short-term exposures (i.e., 24 to 48 h) were performed [128,130,132,133]. PM was shown to affect the physical epidermal barrier in 3D models, as indicated by altered expression of proteins important for epidermal differentiation, such as filaggrin, involucrin, loricrin, and keratins [125,127,129,130,132,133]. Additionally, markers for proliferation, such as Ki67, 5-bromo-2′-deoxyuridine (BrdU) incorporation, and proliferating cell nuclear antigen (PCNA), were shown to be decreased upon PM exposure [125,130].…”
Section: Physical Barriermentioning
confidence: 99%
“…CYP enzymes can metabolize PAHs, and the formed metabolites can induce cell damage either by the formation of DNA, protein adducts, or the generation of ROS [195,[204][205][206][207][208]. Indeed, PM upregulates the CYP enzyme mRNA and protein expression in vitro and in vivo [119,128,129,134,135,139,141,167,171,172,178,187]. Other ROS producing enzymes are the members of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) family [209].…”
Section: Pm Triggers Exogenous and Endogenous Ros Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Iwanaga et al reported that water-in-oil emulsion with natural surfactant can prevent PM-induced inflammation in a reconstructed human epidermis model. 42 While the mechanism of how PM affects skin remains to be elucidated, Jin et al reported that PM, either through the direct penetration of barrier-disrupted epidermis or through hair follicles in intact skin, causes ROS-dependent inflammation in skin. 19 Therefore, there may be three possible ways to protect the skin from harmful effects Based on previous studies and the above concept, the combination of micellar water and barrier cream or antioxidant was expected to show some clinical benefit in participants who were responsive to PM.…”
Section: Discussionmentioning
confidence: 99%
“…It is a genetically determined process that occurs with ageing and is thereby inevitable. This process may be accelerated by environmental factors such as smoking or sun exposure [6][7][8][9], which are factors that are responsible for the so-called extrinsic ageing. Based on these factors [10], we can state that skin ageing is affected by inflammatory factors, hormonal levels, genetic regulation, the production of free radicals [11], exposure to UV radiation, environmental contaminants, etc.…”
Section: Introductionmentioning
confidence: 99%